(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Unlike personal or business cars, Commercial vehicles are mainly utilized for business purpose, When we travel across India we realize that even two wheelers are modified to carry the load. Best examples are ‘Chhakada’ which are used in Gujrat, converted from Rajdoot motor cycle. Three wheelers have their own limitations in terms of speed and load carrying capacity. These are very basic on safety and in terms of style statements. Exactly this chord was captured by Tata Motors while introducing ACE and world has experienced the change that was brought by ACE. Small truck of three wheeler to four wheel added to prestige of the owner. In India, there are two types of truck customers. One who owns it and driven by his driver while on the other hand owner himself is driver. First one is called as fleet owner, hence, needs of fleet owner and owner cum driver differs on many aspects, while essential requirements or basic requirements remains same. In this competitive world, sustaining market is art of doing business for any manufacturer, which is solely dependent on one of important aspect and that is ‘Customers upon fuel prices which keep on fluctuating At the same time, freight charges are not getting updated. So fleet operators demand for fuel efficient trucks and they are ready to pay more for such trucks. Customer satisfaction lies in quick payback while doing business with less fatigue. Thus customer satisfaction becomes trade-off between various needs of the customers. Individual customers with one truck may have different need as he himself driving the truck. He may go for truck with various features. As operator do not drive truck and they appoint drivers, may overlook comfort aspect fleet. Even the truck which is satisfying all the requirements today may not satisfy in coming years as requirements keep on changing because of technology, Government regulations, and business demands. Their money need to get circulated fast to earn the profit. With larger perspective, society is also a customer. It get affected because of smoke and dust pollution, noise pollution. In many road accidents, citizens get killed who are not related to this logistics or transportation business. Manufacturers use the resources of the society and in return they should give back the products which are not harmful for the society and environment. For the subject study external direct customer is considered who invest in truck and who drive the truck to earn his daily bread and butter by doing business. Commercial Truck manufacturing is the business of selling businesses. Every owner in every application should get satisfied with truck he is purchasing. Manufacturer should identify the need of the customer and give option of a truck with specification matching to customer’s needs.